Adjunctive S100A8/A9 Immunomodulation Hinders Ciprofloxacin Resistance in Pseudomonas aeruginosa in a Murine Biofilm Wound Model - Laulund, Anne S.; Schwartz, Franziska; Trøstrup, Hannah; Thomsen, Kim; Christophersen, Lars; Calum, Henrik; Ciofu, Oana; Høiby, Niels; Moser, Claus (Frontiers in Cellular and Infection Microbiology, 2021)
Objective Pseudomonas aeruginosa is known to contribute to the pathogenesis of chronic wounds by biofilm-establishment with increased tolerance to host response and antibiotics. The neutrophil-factor S100A8/A9 has a promising adjuvant effect when combined with ciprofloxacin, measured by quantitative bacteriology, and increased anti- and lowered pro-inflammatory proteins. We speculated whether a S100A8/A9 supplement could prevent ciprofloxacin resistance in infected wounds. Method Full-thickness 2.9cm2-necrosis was inflicted on 32 mice. On day 4, P.aeruginosa in seaweed alginate was injected sub-eschar to mimic a mono-pathogenic biofilm. Mice were randomized to receive ciprofloxacin and S100A8/A9 (n=14), ciprofloxacin (n=12) or saline (n=6). Half of the mice in each group were euthanized day 6 and the remaining day 10 post-infection. Mice were treated until sacrifice. Primary endpoint was the appearance of ciprofloxacin resistant P.aeruginosa. The study was further evaluated by genetic characterization of resistance, means of quantitative bacteriology, wound-size and cytokine-production. Results Three mice receiving ciprofloxacin monotherapy developed resistance after 14 days. None of the mice receiving combination therapy changed resistance pattern. Sequencing of fluoroquinolone-resistance determining regions in the ciprofloxacin resistant isolates identified two high-resistant strains mutated in gyrA C248T (MIC>32µg/ml) and a gyr B mutation was found in the sample with low level resistance (MIC=3µg/ml). Bacterial densities in wounds were lower in the dual treated group compared to the placebo group on both termination days. Conclusion This study supports the ciprofloxacin augmenting effect and indicates a protective effect in terms of hindered ciprofloxacin resistance of adjuvant S100A8/A9 in P.aeruginosa biofilm infected chronic wounds.